2008
DOI: 10.1016/j.bcp.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sensitivity of cholinesterases and [3H]oxotremorine-M binding in heart and brain of adult and aging rats to organophosphorus anticholinesterases

Abstract: Organophosphorus (OP) insecticides elicit toxicity via acetylcholinesterase inhibition, allowing acetylcholine accumulation and excessive stimulation of cholinergic receptors. Some OP insecticides bind to additional macromolecules including butyrylcholinesterase and cholinergic receptors. While neurotoxicity from OP anticholinesterases has been extensively studied, effects on cardiac function have received less attention. We compared the in vitro sensitivity of acetylcholinesterase, butyrylcholinesterase and [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…In contrast to the findings of the present study, several reports indicated that there were no age-related variations for in vitro inhibition of rodent ChEs (Atterberry et al 1997;Mortensen et al 1998a;Padilla 2007;Mirajkar & Pope 2008). Other than species variations, one reason for this discrepancy could be related to external factors (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings of the present study, several reports indicated that there were no age-related variations for in vitro inhibition of rodent ChEs (Atterberry et al 1997;Mortensen et al 1998a;Padilla 2007;Mirajkar & Pope 2008). Other than species variations, one reason for this discrepancy could be related to external factors (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Immediately after thawing, 20 μl aliquots of whole blood were added to four separate 7-ml glass scintillation vials. In two of the vials, 60 μl of 50 mM potassium phosphate buffer, pH 7 (phosphate buffer) was added while in the other two, 60 μl of the specific acetylcholinesterase inhibitor BW 284C51 19 in phosphate buffer was added (final concentration 0.5 μM; this concentration completely inhibited acetylcholinesterase activity under the assay conditions). Samples were vortexed, and then placed into a water bath at 26°C for 60 seconds before adding 20 μl of substrate ([ 3 H]acetylcholine iodide, 1 mM final concentration) in phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples on dry ice were sent to the laboratory of Dr Carey Pope at Oklahoma State University. Total ChE, AChE, and BChE activities were assayed with a modification of the radiometric method of Johnson and Russell, using differential inhibition conditions 18,19 . Immediately after thawing, whole blood was diluted (1:150 in the final reaction) using 50 mM potassium phosphate buffer (PB), pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Total ChE, AChE, and BChE activities were assayed with a modification of the radiometric method of Johnson and Russell, using differential inhibition conditions. 18,19 Immediately after thawing, whole blood was diluted (1:150 in the final reaction) using 50 mM potassium phosphate buffer (PB), pH 7.0. Twenty microliters of diluted whole blood was added to 4 separate scintillation vials.…”
Section: Laboratory Analysis-cholinesterasementioning
confidence: 99%